Behavior Analysis Of COVID-19 Prevention In The Elderly In Jakarta, Tasikmalaya ,and Yogyakarta - Hariyani Sulistyoningsih; Santi Susanti; Tri Budi W Rahardjo; Yeny Sulistyowati; Tri Suratmi; Dini Agustin; Lili Indrawati; Yenni Ariestanti; Nur Apriyan; Rodiyah Rodiyah; Ashish Goel; Ashish Jindal; Alpana Raizada; Maw Pin Tan; George Rebok (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM Universitas Respati Indonesia), 2022)
Background. Covid-19 is a virus that can affect all age groups, including the elderly. The World Health Organization or WHO concluded that this virus is very risky in those aged over 65 years due to a weakened immune system. In addition, the elderly have a higher risk of experiencing a more severe impact than other groups due to degenerative diseases commonly experienced by the elderly. Implementing clean and healthy living behavior as a prevention effort is the main thing to break the chain of transmission of Covid-19. This study aims to determine the prevention behavior of Covid-19 in the elderly and the factors associated with it. Methods. The research design was cross sectional. The sample consisted of men and women aged 60 years or more as many as 135 people. The instrument used is a questionnaire distributed through social media. The data obtained were analyzed by univariate and bivariate using chi square test. results.There is a relationship between age and education with Covid-19 prevention behavior in the elderly with p values of 0.038 and 0.001 respectively. Conclusion. Age and education are related to Covid-19 prevention behavior in the elderly. Keyword : COVID-19, Behavior, Degenerative Disease